Management of patients with implantable cardioverter defibrillators at emergency departments. Issue 2 (24th January 2007) - Liu, Chung-Pin; Ho, Yi-Lwun; Lin, Yen-Hung; Liu, Yen-Bin; Chang, Wei-Tien; Huang, Chien-Hua; Chen, Wen-Jone
Abstract : Background: With rapid improvements in technology and accumulation of clinical evidence, the implantable cardioverter defibrillator (ICD) has become a standard treatment for either primary or secondary prevention of sudden cardiac death. However, no analysis based on the perspective of emergency department has been reported, and managing patients with ICD remains a challenge to the emergency department doctors. Methods: This study reviewed the emergency department visits of patients who received ICD implantation in a single university hospital from 1995 to 2004. The baseline demographic and laboratory data were compared between groups with the non-parametric method of the Mann–Whitney U test for continuous data and the χ 2 test for categorical data; p<0.05 was considered significant. Results: 81 patients (56 men and 25 women) were included in this study. 43% of patients had at least one emergency department visit during the follow-up period, and a total of 86 emergency department visits were recorded. The most frequent aetiology of emergency department visits was ICD discharge (37 episodes; 43.1%) and the most frequent presenting symptom was electric shock sensation (25 episodes; 29.1%). Only 11 (12.8%) emergency department visits were because of non-cardiac aetiologies. Patients with emergency department visits had significant lower left ventricular ejection fraction (mean (SD) 41.5 (19.8) v 55.2 (18.4) ejection fraction units; p = 0.005) and more use of warfarin (8.6% v 0%; p<0.05). Although most emergency department visits were device or arrhythmia related, the acute coronary syndrome and congestive heart failure still accounted for 27.9% of hospital returns in combination. Conclusions: Defibrillator discharge, acute coronary syndrome and heart failure constitute most aetiologies of emergency department visits of patients with ICD. The risk factors include lower left ventricular ejection fraction and use of warfarin.